KEMAMPUAN REPRESENTASI MATEMATIK SISWA KELAS IX MTS PADA MATERI BANGUN RUANG SISI LENGKUNG DENGAN PENERAPAN PENDEKATAN RECIPROCAL TEACHING - Moka, Santriwati; Hendriana, Heris; Afrilianto, M (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The purpose of this study is to analyze the influence of  implementing reciprocal teaching approach as an attempt to improve students’ mathematical representation in class IX-B MTs Al-Musyahadah Cimahi on the curved-face three-dimensional-object. The type of research, which applied, is classroom action research. The classroom action research consists of 2 (two) cycles based on teaching syllabus of the mathematics teacher in class IX-B. Each cycle was conducted based on the learning objectives. The cycle in this study involved the following procedures: (1) Planning; (2) Implementation of action; (3) Observation and evaluation; (4) Reflection. Based on the result of research conducted on the students of class IX-B MTs Al-Musyahadah on the curved-face three-dimensional-object  material, it revealed the fact that the use of reciprocal teaching approach can improve the ability of mathematical representation, which are;  (1) responses and learning outcomes shown in cycle II are primly good, and (2) the students’ score of mathematical representation test capability in each cycle has improve significantly, until 87% on the last cycle . Moreover, the results showed that there are only 4 students from total 29 students who obtain score below 65. Therefore, Learning by applying reciprocal teaching approach is very effective to use in learning process.